Growth Mindset in the Lens of Social-Cognitive Approaches: The Critical Role of Cultural Values, Parental Involvement, and Teacher Engagement - Kholili, Ma'rifatin Indah; Rusmana, Nandang; Ahman, Ahman; Budiman, Nandang; Suryawati, Citra Tectona (Bulletin of Counseling and Psychotherapy, 2025)
This study investigates the factors influencing the growth mindset of high school students in Surakarta through a social-cognitive perspective. Employing a mixed-method approach with an explanatory sequential design, the research examined the linear relationship between parental involvement, teacher engagement, and cultural values with students’ growth mindsets, while also exploring educators’ perspectives and integrating quantitative and qualitative findings. Participants included 395 students and 24 educators (guidance and counseling teachers and principals). The instruments consisted of self-assessment scales measuring growth mindset, cultural values, perceptions of parental involvement and teacher engagement, along with narrative inquiry interviews. Quantitative analysis revealed a significant linear relationship between the three independent variables and students’ growth mindset. Classical assumptions were met, including normality (p = 0.058 > 0.05), absence of multicollinearity (VIF < 10), homoscedasticity, and no autocorrelation (Durbin-Watson = 2.056). Multiple regression analysis confirmed the model’s feasibility (F = 68.045, p < 0.001), with the three predictors jointly explaining 34.3% of variance (R² = 0.343). Individually, cultural values showed the strongest effect (β = 0.400, t = 9.120, p < 0.001), followed by parental involvement (β = 0.203, t = 4.218, p < 0.001) and teacher engagement (β = 0.154, t = 3.236, p = 0.001). Qualitative analysis identified five themes: intrinsic motivation, life goals, cultural and family influences, the role of teachers and schools, and social support. The integrated findings suggest that growth mindset is ecosystemic, shaped by interactions of personal, behavioral, and environmental factors. This study extends understanding of growth mindset within the Indonesian, particularly Javanese, cultural context and provides practical implications for educational interventions.